The Analytics of Uncertainty and Information - Bikhchandani, Sushil; Hirshleifer, Jack; Riley, John G. (Cambridge : Cambridge University Press, 2013)
There has been explosive progress in the economic theory of uncertainty and information in the past few decades. This subject is now taught not only in departments of economics but also in professional schools and programs oriented toward business, government and administration, and public policy. This book attempts to unify the subject matter in a simple, accessible manner. Part I of the book focuses on the economics of uncertainty; Part II examines the economics of information. This revised and updated second edition places a greater focus on game theory. New topics include posted-price markets, mechanism design, common-value auctions, and the one-shot deviation principle for repeated games.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Uncertainty; Equilibrium (Economics); Decision making; Information theory in economics